Involvement of peripheral vasomotor fibres in carpal tunnel syndrome. Issue 7 (July 1979) - Aminoff, M J
Abstract : It is often assumed that large diameter nerve fibres are affected selectively in patients with compressive peripheral nerve lesions. However, in five of 13 patients with the carpal tunnel syndrome, plethysmography revealed that the normal digital vasoconstrictor response to inspiration was abolished in the index finger but preserved in the little finger of the affected hand. This indicates that the function of sympathetic efferent fibres destined for a median-innervated digit is sometimes disturbed also in patients with median nerve entrapment at the wrist.